The effects of melatonin on the striatum - BORACI, HATİCE; KİRAZLI, ÖZLEM; YILDIZ, SERCAN DOĞUKAN; ŞEHİRLİ, ÜMİT SÜLEYMAN (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Some of the neurological diseases cause morphologic changes in the striatal neurons. Medial forebrain bundle (MFB) lesion is a commonly used method to produce a Parkinsonian model rat. Melatonin is a hormone which exerts a neuroprotective effect on the neurons. The aim of this study is to investigate the effect of melatonin on the dendritic morphology of striatal medium spiny neurons (MSNs) in rats with MFB lesion. Materials and Methods: Twelve male Wistar albino rats were given saline injections into the MFB and divided into sedentary and treatment groups. The treatment group was administered a 10 mg/kg dose of melatonin intraperitoneally for 30 days. The lesion was confirmed histologically by Nissl staining. Golgi staining technique was applied to observe neuronal morphology. Neuronal structures were analysed from three-dimensional images by Neurolucida (MBF Bioscience) software. Results: The MFB lesion caused a reduction in the total dendritic length and in the number of dendritic endings. The melatonin enhanced the number of dendritic endings compared to the sedentary group. The melatonin led to an increase in the total spine density, spine densities of thin and mushroom types. Conclusion: Melatonin improved the dendritic degeneration due to MFB lesion.
Keywords: Dendritic spine; Melatonin; Golgi; Neurolucida; DENDRITIC SPINE PATHOLOGY; L-DOPA; NEURONS; MORPHOLOGY; DENSITY; PLASTICITY; CORTEX